Faktor Penyebab Pengguna Narkotika di Kalangan Masyarakat - Oktir Nebi (Wajah Hukum, 2019)
Drug abuse also affects the body and mental-emotional of its users. If it is consumed more often, especially in excess amounts it will damage the health of the body, psyche and social functions in the community. The influence of drugs on adolescents can even have more fatal consequences, because it inhibits his personality development. Narcotics can damage one's potential, because it is considered a "reasonable" way for someone to deal with and solve problems in daily life. Not apart from the various problems faced are seen from several factors 1) Frustration because they do not get a job 2) Lack of information about the danger of sabu-sabu abuse 3) The nature of adolescents who are easily influenced by friends or the environment. In this scientific writing research, the type of research used is normative juridical research. The approach used is the conceptual approach (conceptual approach) and the legal approach (statute approach). Prevention that can be done with Primary Prevention (Primary Prevention), Secondary Prevention (Secondary Prevention), Tertiary Prevention (Tertiary Prevention).